Epidemiology of Human Monkeypox about the 2022 Outbreak: A Narrative Review - Aliasghar Fakhri-Demeshghieh; Hesameddin Akbarein; Parsa Almasi (Journal of Community Health Research)
Abstract:  Human Monkeypox is a zoonotic disease caused by 2 distinct clades of human monkeypox virus (MPXV). MPXV infections can cause several clinical symptoms including fever, skin rash, back pain, and lymphadenopathy in humans. Even though MPXV infections are generally self-limiting, death is possible and fatality due to MPXV infections in humans is 3-6 percent. While the disease is endemic to Africa, its potential to cause outbreaks in other continents has been observed. The natural reservoir of MPXV in Africa and the full host range of the virus are not known, but rodents are suggested to be the reservoirs. The transmission of MPXV occurs via close contact and the prevention strategies include avoiding close contact and post-exposure prophylactic vaccination of people at risk with smallpox vaccines. In this study, the most recent information about the epidemiology of MPXV about the latest research on the 2022 outbreak of MPXV has been reviewed.